2014
DOI: 10.3389/fmicb.2014.00383
|View full text |Cite
|
Sign up to set email alerts
|

Effect of crude plant extracts from some Oaxacan flora on two deleterious fungal phytopathogens and extract compatibility with a biofertilizer strain

Abstract: The antimicrobial activity of 12 plant extracts was tested against the phytopathogens Alternaria alternata and Fusarium solani. In addition, the compatibility of the extracts toward Bacillus liqueniformis, a biofertilizer and a non-target microorganism, was assessed. Plants tested belong to the Euphorbiaceae, Asteraceae, Crassulaceae, Rubiaceae, Convolvulaceae, Verbenaceae, Orchidaceae, Nyctaginaceae, Boraginaceae, and Tiliaceae families and were collected in the State of Oaxaca. The antifungal activity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 52 publications
0
17
0
1
Order By: Relevance
“…and Fusarium sp. [35] is very important for the establishment of field crops. These pathogens can cause much damage and have the ability to infect a wide range of hosts [36].…”
Section: Effect Of Pyroligneous Extract Treatmentmentioning
confidence: 99%
“…and Fusarium sp. [35] is very important for the establishment of field crops. These pathogens can cause much damage and have the ability to infect a wide range of hosts [36].…”
Section: Effect Of Pyroligneous Extract Treatmentmentioning
confidence: 99%
“…However, some countries have avoided the use of these fungicides (RamosGarcía et al, 2012). In recent years, the indiscriminate use of synthetic fungicides to control postharvest diseases in fruit has attracted international concern about significant negative impacts on human health and the environment, as well as the emergence of fungicide-resistant strains (Lira-De León et al, 2014). Thus, many researchers have been investigating safe alternative substances to reduce or even replace the use of synthetic fungicides in fruit (Liu, Tian, Meng, & Xu, 2007;Sánchez-González, Chafer, Chiralt, & González-Martínez, 2010).…”
mentioning
confidence: 99%
“…The use of A. aurantium to treat intestinal diseases suggested that it could have antiamoebic activity. Lira-De León et al (2014) previously suggested that ethyl acetate extract from the root was more active than the methanolic extract from the aerial part against fungi. In this work, we decide to analyze the effect on the proliferation of E. histolytica trophozoites, of a methanolic extract of the aerial part ( Aa MeA), a methanolic extract of the root ( Aa MeR) and an ethyl acetate extract of the root ( Aa EaR), all of them at 200 μg/ml.…”
Section: Resultsmentioning
confidence: 98%
“…Rob., Inula aurantiaca (L.) Spreng., and Tagetes punctate Sessé & Moc 1 . Antimicrobial activity from this plant has been reported against Micrococcus luteus , Bacillus cereus, Staphylococcus epidermidis, Pseudomonas aeruginosa, Alternaria alternata , and Fusarium solani ; it is also reportedly innocuous toward cell lines such as KB (human nasopharyngeal carcinoma), Caco-2 (human colon carcinoma) and Bacillus liqueniformis ( Frei et al, 1998 ; Lira-De León et al, 2014 ). Aerial parts of this vegetable species are used among Zapotec Indians (healers, midwives, and herbalists) to cure the stomachache ( Frei et al, 1998 ).…”
Section: Introductionmentioning
confidence: 99%